“ Kejahatan Stellionaat ” - Redho Junaidi (KEADILAN PROGRESIF, 2012)
Crime "stellionaat" which means the crime in respect of goods not moving (onroerende goederen). What is meant by the goods do not move it, especially land, rice fields, and buildings. The main element in stellionaat crime is an act that prohibited acts include selling, trading, saddled with dependents, rent, mortgage, and object actions are prohibited include: the right to use land, building/ construction and plant seedlings on land owned, while knowing that another person have rights to land and goods thereon.